“Words Matter”: A Case Against CoronaVocab in Traumatic Times (Balthazar, 2020)
Language is a way to behave and influence our environment. A good example of the importance of what we say is what we are experiencing during the current pandemic: instead of staying united more than ever and thinking that we are in this together, the words we use are actually keeping us apart because all they convey is violence, incitement to a war (against the virus, against one another) and the actual desire to practice social distancing. The current war on virus is modeled on the war on drugs; brute force is and always will be an essential part of politics because it serves its purpose, which is to manipulate people.